STBA STUDENTS PROBLEM IN TRANSLATING PHRASAL VERB AND COLLOCATION TO INDONESIA - Magpika Handayani (STBA Pontianak, 2019)
This study aim at analyzing students problem in translating text in English into Bahasa Indonesia as the target language. Translating from English to Indonesia as target language is also a problem for students. There are a lot of things must be considered by students so that the result of translation equivalent with target language message. The differences of phrasal verb and collocation in English with the target language meaning may cause difference information obtained by the reader, and as a consequences, the information might mislead the reader. STBA is one of campus in Pontianak which provides students with English skill and translation skill. In doing translation, students need to think so many aspects when translating the sentences or the conversation into their native language in order to the result of the translation sounds natural. The method in this writing is descriptive method, and the writer describe students' problems in translating text from English into Bahasa Indonesia as a target language and gathering information related to the problems faced through interview. The result of the observation shows that the difference between English phrasal verb and collocations with Indonesia equivalent words become the main problem in giving the meaning in the target language, therefore students need to understand the category and the function in phrasal verb and collocation in English in order to find equivalent meaning in Indonesian.